TOXICOLOGY OF HEAVY METALS AND THEIR IMPACT ON HUMAN HEALTH - Ajieva, Muxabbat Baxtibaevna; Ajieva, Zuxra Baxtibaevna; Nurimbetov, Ilyas Ansatbaevich (SCIENCE and SOCIETY, 2026)
The article provides information about the new science - ecology and the problems associated with pollution of the environment with harmful chemicals ("poisons"), the names of which are familiar to everyone (dioxins, PVC, DDT, lead, mercury, etc.); their impact on living organisms; information on how to protect yourself from this impact. The article is also informative and can serve as a reference for specialists, environmental activists, and students of various specialties.
Keywords: ecology; chemicals; poisons; metals; lead; mercury; cadmium; copper; arsenic; zinc